Random Walk Hypothesis: An Empirical Comparison of Shari’ah and Non-Shari’ah Capital Markets of Pakistan and China - Shehryar, Muhammad; Bashir, Furrukh; Raza, Kashif; Ahmad, Rashid (iRASD Journal of Economics, 2022)
The instant research comparatively determines the weak-form informational efficiency of Shari’ah and corresponding non-Shari’ah equity indices of Pakistan and China by testing the Random Walk Hypothesis. For this purpose, this study employed the Automatic Variance Ratio on the daily index data for the time ranging from 1st July 2009 to 30th June 2018. The findings of the study show that the Shari’ah index of Pakistan (KMI-30) is informational efficient in weak-form but the Shari’ah index of China (FTSE Shariah China Index) is not efficient. On the other hand, as far as the non-Shari’ah indices are concerned, KSE-100 Index (Pakistan) is not weak-form efficient, but the Shanghai Composite Index (China) is efficient. So, it is determined that in Pakistan, the Shari’ah equity market is weak form efficient during the sample period but its counterpart non-Shari’ah equity market is not efficient. Further, in China, the non-Shari’ah stock market is weak-form efficient, but its Shari’ah stock market is not efficient. In the nutshell, it is concluded that the Shari’ah indices are also witnessing efficiency along with non-Shari’ah indices, and Shari’ah indices viz-a-viz Shari’ah stocks can be good option for optimum investment.